Model predictive control of discrete T-S fuzzy systems with time-varying delay - Teng, Long (2020)
Robust model predictive control of discrete nonlinear systems with bounded time-varying delay and persistent disturbances is investigated in this paper. The T-S fuzzy systems are utilized to represent nonlinear systems. A Razumikhin-type Lyapunov function is adopted for time-delay systems due to its advantage in reducing the complexity especially for systems with large delays and disturbances. The robust positive invariance set theory for systems subjected to time-varying delay and disturbances is analyzed. In addition, the input-to-state stability is realized due to persistent disturbances. The controller synthesis conditions are derived by solving a sequence of matrix inequalities. Simulation on a continuous stirred-tank reactor (CSTR) is illustrated to verify the effectiveness of the proposed method.